Review on continuous nursing of ulcerative colitis (溃疡性结肠炎延续护理的研究进展) - XU Bing (许冰); LIU Miao (刘苗); QI Huan (祁欢); TIAN Yajuan (田亚娟); SHI Xiaojun (石晓君); HU Hairong (胡海荣) (Association of Integrative Nursing, 2021)
It is recognized that continuous nursing is of great significance to reduce the recurrence rate of patients with ulcerative colitis, improve the quality of life of patients and save social resources. This paper reviews the continuous nursing of ulcerative colitis, including follow-up time, follow-up methods, contents of education and so on, hoping to provide reference and guidance for clinical medical staff. (延续护理对溃疡性结肠炎患者的愈后康复有重要作用。本文对溃疡性结肠炎患者延续护理的回访时间、回访方法、宣教内容等进行了总结, 以期望为临床医务人员提供参考和指导。)